Overlapping multivoxel patterns for two levels of visual expectation - de Gardelle, Vincent; Stokes, Mark G.; Johnen, Vanessa M.; Wyart, Valentin; Summerfield, Christopher (Frontiers in Human Neuroscience, 2013)
According to predictive accounts of perception, visual cortical regions encode sensory expectations about the external world, and the violation of those expectations by inputs (surprise). Here, using multi-voxel pattern analysis (MVPA) of functional magnetic resonance imaging (fMRI) data, we asked whether expectations and surprise activate the same pattern of voxels, in face-sensitive regions of the extra-striate visual cortex (the fusiform face area or FFA). Participants viewed pairs of repeating or alternating faces, with high or low probability of repetitions. As in previous studies, we found that repetition suppression (the attenuated BOLD response to repeated stimuli) in the FFA was more pronounced for probable repetitions, consistent with it reflecting reduced surprise to anticipated inputs. Secondly, we observed that positive- and negative-going responses to repetition were both consistent across scanner runs, suggesting that both have functional significance, with repetition enhancement possibly indicating the build up of sensory expectation. Critically, we also report that multi-voxels patterns associated with probability and repetition effects were significantly correlated within the left FFA. We argue that repetition enhancement responses and repetition probability effects can be seen as two types of expectation signals, occurring simultaneously, although at different levels (lower vs. higher), and different time scales (immediate vs. long term).